Low-Temperature Synthesis of Superconducting Nanocrystalline MgB2. (21st February 2011) - Lu, Jun; Xiao, Zhili; Lin, Qiyin; Claus, Helmut; Fang, Zhigang Zak
Abstract : Magnesium diboride (MgB2 ) is considered a promising material for practical application in superconducting devices, with a transition temperature near 40 K. In the present paper, nanocrystalline MgB2 with an average particle size of approximately 70 nm is synthesized by reacting LiBH4 with MgH2 at temperatures as low as 450 ° C. This synthesis approach successfully bypasses the usage of either elemental boron or toxic diborane gas. The superconductivity of the nanostructures is confirmed by magnetization measurements, showing a superconducting critical temperature of 38.7 K.